2015
DOI: 10.1542/peds.2015-1400
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Health and Developmental Outcomes After Cesarean Birth in an Australian Cohort

Abstract: BACKGROUND AND OBJECTIVES: Concerns have been raised about associations between cesarean delivery and childhood obesity and asthma. However, published studies have not examined the long-term neurodevelopmental outcomes or fully addressed confounding influences. We used data from the LSAC (Longitudinal Study of Australian Children) to explore the relationship between cesarean delivery and physical and socio-emotional outcomes from 0 to 7 years, taking into account confounding factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 34 publications
3
15
1
1
Order By: Relevance
“…Our results are consistent with other studies regarding full-term, preterm, breech presentation children or twins, and these studies also found no significant difference in developmental and behavioral outcomes between cesarean and vaginal-delivered groups (Asztalos et al, 2016; Bahl et al, 2007; Dekeunink et al, 2016; Haque et al, 2008; Joseph et al, 2015; Kimura et al, 2017; Robson et al, 2015; Spinillo et al, 1992; Zhu et al, 2014). However, previous studies have found some negative outcomes due to cesarean delivery.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are consistent with other studies regarding full-term, preterm, breech presentation children or twins, and these studies also found no significant difference in developmental and behavioral outcomes between cesarean and vaginal-delivered groups (Asztalos et al, 2016; Bahl et al, 2007; Dekeunink et al, 2016; Haque et al, 2008; Joseph et al, 2015; Kimura et al, 2017; Robson et al, 2015; Spinillo et al, 1992; Zhu et al, 2014). However, previous studies have found some negative outcomes due to cesarean delivery.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, it usually takes 5–7 days for women to get recovered after cesarean section (Donowitz & Wenzel, 1980; Rortveit et al, 2003). Therefore, women after vaginal delivery have more time and energy to take care of the newborn and establish a good maternal-child interaction, which may benefit neonatal neurological development (Robson et al, 2015; Rowe-Murray & Fisher, 2001). In addition, women after vaginal delivery have fewer complications (Arikan et al, 2012) and can begin breastfeeding sooner than cesarean born infants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…non‐medically indicated nullipara, low‐risk multiparous) have contributed to the mixed findings. Whether an association is manifested at younger or older ages is conflicting , and our dataset has too few children at older ages to examine this issue.…”
Section: Exposurementioning
confidence: 99%
“…In contrast, it usually takes 5-7days for women to get recovered after cesarean section (Donowitz ,Wenzel 1980;Rortveit et al 2003). Therefore, women after vaginal delivery have more time and energy to take care of the newborn and establish a good maternal-child interaction, which may benefit neonatal neurological development (Robson et al 2015;Rowe-Murray ,Fisher 2001).…”
Section: Introductionmentioning
confidence: 99%